Membangun Kreativitas dan Sikap Profesional Mahasiswa Calon Guru Matematika pada Mata Kuliah Simulasi Mengajar - Tri Nova Hasti Yunianta (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
The purpose of this qualitative descriptive research is to describe the professional attitude and creativity building of mathematics student teachers during the microteaching course. The study was conducted on May 8, 2017 until June 23, 2017. There were 17 students from Mathematics Education Study Program, Faculty of Teacher Training and Education, Satya Wacana Christian University. Data collection techniques used the observation methods, open questionnaires, and documentation. The training is to build a professional attitude, begins with the exercise of disciplinary rules in which the student must arrive on time, wear the appropriate shirts as the faculty suggested, collect the tasks of the learning device on time, and for later attire, students have to wear white shirts, black trouser/ long skirt, blazer, pantofel boots, and a tie for both male and female, except the ones with hijabs. The training to build students' creativity begins by creating an exciting way of learning, planning the contents of learning with contemporary models that are currently developing, making closing activities in accordance with selected learning models, making lesson plans equipped with presentation slide with specific slide limits, creating a worksheet that can keep students active with certain page number limitation, then students may create additional other learning medias. Performing those attitude, blended with well-designed stages, the students can feel there is a change in themselves. Changes in attitudes and experiences experienced by students in this learning are the focus of this qualitative research description.